1978
DOI: 10.1007/bf01892405
|View full text |Cite
|
Sign up to set email alerts
|

The genetic control of antibody variable regions in the mouse

Abstract: The genetic control of the variable (V) 1 regions of mouse antibodies is being analysed at several levels. The direct chemical analysis of V-region genes is underway [87]; antibody V-genes have been isolated from the D N A of differentiated and undifferentiated mouse cells and are now being sequenced. These studies already provide support for the conclusions based on analysis of amino acid sequences of V-regions and the genetic analysis of V-region genes using markers such as idiotype. In this chapter, we will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 80 publications
2
47
0
Order By: Relevance
“…Drawing tive B cells and thus are preferentially selected and expanded. Lsive studies of other CRI systems (26)(27)(28), we Recently it has been shown that immunization of adults with -CRI defined by our anti-Id reagent is serving as Hib PS generally results in an increase in antibody avidity (31). iarker for a family of structurally related V do-An interesting group of subjects were the five adults who were rh prevalence of the CRI in an outbred popula-negative for CRI in both pre-and postimmunization sera.…”
Section: Smentioning
confidence: 99%
“…Drawing tive B cells and thus are preferentially selected and expanded. Lsive studies of other CRI systems (26)(27)(28), we Recently it has been shown that immunization of adults with -CRI defined by our anti-Id reagent is serving as Hib PS generally results in an increase in antibody avidity (31). iarker for a family of structurally related V do-An interesting group of subjects were the five adults who were rh prevalence of the CRI in an outbred popula-negative for CRI in both pre-and postimmunization sera.…”
Section: Smentioning
confidence: 99%
“…The V region gene segments, Igh-V or V H , have posed a larger challenge; estimates of their numbers range from hundreds to thousands (7)(8)(9)(10). Genetic mapping experiments indicated that the locus is a centimorgan or larger (11)(12)(13), suggesting a sequence size of several million base pairs of DNA, consistent with a gene content of hundreds to thousands of coding elements. Detailed studies of the organization of V H gene families by Brodeur and colleagues (14) have provided a better understanding but much remains to be elucidated.…”
mentioning
confidence: 99%
“…To demonstrate the genetic specificity of the BALB/c anti-CB-20 antiserum, the reactivity was investigated by the dye exclusion cytotoxic assay on thymocytes derived from various strains of mice including allotype congenic mice: (19).…”
Section: Genetic Specificity Of Balb/c Anti-cb-20 Antiserummentioning
confidence: 99%